2022
DOI: 10.1177/13694332221095629
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage damage identification method based on fractal theory and whale optimization algorithm

Abstract: Structural damage identification based on time domain method of vibration response has been widely developed in the recent decades, however, it still confronts some difficulties, such as measurement noise and model error. This paper proposes a novel two-stage damage identification method based on fractal dimension and whale optimization algorithm (WOA). In this study, based on vibration data, the difference in curvature of fractal dimension (DCFD) is used as the damage index to identify the location of suspici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The experimental results showed that the proposed method was effective without noise, but it was slightly sensitive to noise when quantifying the damage degree. Later, Huang et al [159] proposed a new objective function based on fractal dimension (FD) for WOA. In the simulation test, WOA could effectively identify the damage degree under noise conditions.…”
Section: Meta-heuristic Optimization Algorithmmentioning
confidence: 99%
“…The experimental results showed that the proposed method was effective without noise, but it was slightly sensitive to noise when quantifying the damage degree. Later, Huang et al [159] proposed a new objective function based on fractal dimension (FD) for WOA. In the simulation test, WOA could effectively identify the damage degree under noise conditions.…”
Section: Meta-heuristic Optimization Algorithmmentioning
confidence: 99%
“…Genetic Algorithm [59] The first one used in SDD Particle Swarm Optimization [60] Elite orientation for position updating Cuckoo Search [61,62] Random elimination mechanism Jaya Optimization [63,64] Parameter-free Moth-flame Optimization [65,66] Logarithmic spiral function for position updating Whale Optimization [67][68][69] Sunflower Optimization [70] Inverse square law radiation and random pollination Echolocation Search Algorithm [71] Dislocalization technique to avoid local optima Tug-of-war optimization [72] Originally proposed for SDI Gray Wolf optimization [73] Gray wolf hierarchy for the selection of the best agent Experience-based Learning (EBL) algorithm [74] Two modes to balance the exploration and exploitation Improved Optimization Tools PSO-CS [75] Better global search performance (PSO)-Simplex Algorithm [76,77] Improvement in the local search Enhanced MFO [78] Both global and local search abilities are enhanced Hybrid Jaya and Tree Seeds Algorithm [79] Avoiding local minimal Improved Jaya algorithm [80] Clustering strategy to enhance the global optimization capability Huang et al [59] introduced a genetic algorithm and an objective function constructed based on frequencies and mode shapes with different weight coefficients to address the issue of damage identification considering varying temperature effects. A three-span continuous beam and a two-span steel grid under temperature variation conditions were exploited to validate the method's feasibility.…”
Section: Optimization Toolsmentioning
confidence: 99%
“…Structural damage identification (SDI), as an important part of structural health monitoring (SHM), aims to identify structural damage timely. During several decades, many methods have been proposed to solve this problem, one of the most popular is the vibration-based damage identification (VBDI) method (Guo et al, 2020; Huang et al, 2022). Although this kind of method has obtained good results, it still faces a challenge, namely, some external interference in the natural environment will cause fluctuations of measured dynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%